1996
DOI: 10.1002/pssb.2221970107
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of Grüneisen parameter in solids

Abstract: Making the assumption that the value of the second Griineisen parameter q is constant, we present a relation for the pressure dependence of the Griineisen parameter y. The tests on four solids (NaCl, Li, Na, and K) show that the agreement between the calculated results given by the relation and the experimental data on the pressure dependence of y is excellent. A comparison between the linear relation suggested by Kumari and Dass and the relation presented in this paper demonstrates that the latter is better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…where q 0 and B 0 are the Debye temperature and the isothermal bulk modulus at zero pressure, respectively, b T is the first-order pressure derivative of B T and Recently, Zheng-Hua Fang [4] presented another expression for the pressure dependence of the Gru È neisen parameter g using the assumption that the value of the second Gru È neisen parameter q is a pressure-independent constant. This relation is written as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where q 0 and B 0 are the Debye temperature and the isothermal bulk modulus at zero pressure, respectively, b T is the first-order pressure derivative of B T and Recently, Zheng-Hua Fang [4] presented another expression for the pressure dependence of the Gru È neisen parameter g using the assumption that the value of the second Gru È neisen parameter q is a pressure-independent constant. This relation is written as…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the comparison [4] between the two different relations (3) and (6) for the pressure dependence of g has demonstrated that the latter is better, we think that the new relation for the pressure dependence of q should also be better. Therefore, in this paper we first derive the new expression for the pressure dependence of q, then apply it to the cases of NaCl and CsI crystals in view of the results on the two solids given by (4) have been reported in the literature [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The approaches to solve the problems involved are based on first-principles theoretical calculation [15], classical molecular dynamic simulation [15]; direct ab initio methods [16] and phenomenological predictions [6,17]. We note that the results based on the method that combines firstprinciples and classical molecular dynamic simulation agree with the results of shock compression experiments [15].…”
Section: Calculations and Discussionmentioning
confidence: 51%
“…(3) requires q to be a function of V. We think that, perhaps, the form of the function is just the Eq. (6).…”
Section: Calculations and Discussionmentioning
confidence: 95%
See 1 more Smart Citation